2008
DOI: 10.4142/jvs.2008.9.4.395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of partial cranial cruciate ligament rupture with positive contrast computed tomographic arthrography in dogs

Abstract: Computed tomographic arthrography (CTA) of four cadaveric canine stifles was performed before and after partial cranial cruciate ligament rupture in order to verify the usefulness of CTA examination for the diagnosis of partial cranial cruciate ligament rupture. To obtain the sequential true transverse image of a cranial cruciate ligament, the computed tomography gantry was angled such that the scanning plane was parallel to the fibula. True transverse images of cranial cruciate ligaments were identified on ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
1
14
1
Order By: Relevance
“…There are several published studies describing the use of stifle CTA in canine cadavers. These have described the normal intra‐articular anatomy as seen on CTA (Samii and Dyce 2004, Soler and others 2007) and also demonstrated that CTA can be used to diagnose CCL rupture (Han and others 2008) and medial meniscal injury (Tivers and others 2008) in cadavers. The cadaver study by Tivers and others (2008) showed that dorsal CTA images had a sensitivity of 90 per cent and a specificity of 100 per cent for the diagnosis of simulated injuries of the caudal horn of the medial meniscus.…”
Section: Introductionmentioning
confidence: 99%
“…There are several published studies describing the use of stifle CTA in canine cadavers. These have described the normal intra‐articular anatomy as seen on CTA (Samii and Dyce 2004, Soler and others 2007) and also demonstrated that CTA can be used to diagnose CCL rupture (Han and others 2008) and medial meniscal injury (Tivers and others 2008) in cadavers. The cadaver study by Tivers and others (2008) showed that dorsal CTA images had a sensitivity of 90 per cent and a specificity of 100 per cent for the diagnosis of simulated injuries of the caudal horn of the medial meniscus.…”
Section: Introductionmentioning
confidence: 99%
“…The modality of choice for imaging the human knee is MRI; however, CTA has been reported to have similar sensitivity and specificity to MRI for detection of meniscal injury 92 . Successful identification of intraarticular structures has been reported with CTA in normal 93 and cadaveric canine stifles 94,95 . Care during administration of intraarticular contrast to avoid the fat pad and a concentration of 150 mg iodine/mL is recommended to enhance visualization without contrast obscuring structures because of excessive bloom 93 .…”
Section: Ctmentioning
confidence: 99%
“…92 Successful identification of intraarticular structures has been reported with CTA in normal 93 and cadaveric canine stifles. 94,95 Care during administration of intraarticular contrast to avoid the fat pad and a concentration of 150 mg iodine/mL is recommended to enhance visualization without contrast obscuring structures because of excessive bloom. 93 Removal of a small amount of joint fluid, especially in dogs with severe joint effusion, and flexing and extending the joint gently has been recommended to enhance contrast dispersion.…”
Section: Ctmentioning
confidence: 99%
See 1 more Smart Citation
“…It offers improved soft tissue contrast and detail compared to computed tomography. While computed tomographic arthrography has been used to identify partial rupture of the cranial cruciate ligament in dogs, MRI offers additional information regarding the soft tissue structures . Magnetic resonance imaging of the normal stifle in dogs using low‐filed MRI has been described .…”
Section: Introductionmentioning
confidence: 99%